OMCTH 2022 - Cover and Table of contents - Redakcja (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2022)
Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders vol. XXVII (2022) Editorial Team Roman Czaja, Editor in Chief, Uniwersytet Mikołaja Kopernika w Toruniu Jürgen Sarnowsky, Editor in Chief, Universität Hamburg Krzysztof Kwiatkowski, Associate Editor, Uniwersytet Mikołaja Kopernika w Toruniu Anna Maleszka, Assistant Editor, Uniwersytet Mikołaja Kopernika w Toruniu Editorial Board Jochen Burgtorf, California State University Sylvain Gouguenheim, L’École normale supérieure de Lyon Hubert Houben, Università del Salento Lecce Gregory J. Leighton, Cardiff University Alan V. Murray, University of Leeds Scientific Council Udo Arnold, Emeritus, Rheinische Friedrich-Wilhelms-Universität Bonn Karl Borchardt, Monumenta Germaniae Historica, München Helen Nicholson, Cardiff University Maria Starnawska, Uniwersytet Przyrodniczo-Humanistyczny w Siedlcach Kristjan Toomaspoeg, Università degli Studi di Lecce Technical Editing and Proofreading: Krzysztof Kwiatkowski, Anna Maleszka, Danuta Murawska, Gregory Leighton, Marta Palczewska Translations: Marta Palczewska Table of contents Studies and articles from the 21st Ordines Militares Conference Helen J. Nicholson (Cardiff) Dominus Jhesus novum genus militie constituit et elegit: “the Lord Jesus has set up and chosen a new sort of knighthood”. The Military Orders’ Relations with Women from the twelfth to the sixteenth century ‒ a Survey Maria Soledad Ferrer-Vidal Díaz del Riguero (Madrid) Nobility, kinship and memory in Santa Eufemia de Cozuelos, the first female convent of the Military Order of Santiago Marie-Anna Chevalier (Montpellier) Military orders and powerful women in the Christian Levant Kristjan Toomaspoeg (Lecce) The nunneries of the Order of St. John in medieval Italy Karl Borchardt (München) Notizen zu Johanniterschwestern in Mitteleuropa (außerhalb von Friesland) während des Spätmittelalters Maria Starnawska (Siedlce) Die Johanniter und die weiblichen Orden in Schlesien im Mittelalter Nicholas Coureas (Nicosia) Women and the Hospitaller Order on Rhodes and Cyprus in the fourteenth and fifteenth centuries Other studies Piotr Gotówko (Fribourg/Freiburg) Die Beziehungen des Deutschen Ordens zu den Grafen von Kyburg und zur Stadt Bern in der ersten Hälfte des 13. Jahrhunderts Przemysław Waszak (Toruń) Saint Bridget of Sweden and the Teutonic Knights. Her Revelations in the context of the Gothic crucifix from the Holy Trinity Cathedral in Kulmsee (Chełmża) and the legacy of other mystics Jürgen Sarnowsky (Hamburg) Sancta obedientia. Die Rolle des Gehorsams in den geistlichen Ritterorden des ausgehenden Mittelalters Book reviews and book notices Die Replik auf die Erwiderung von Christofer Herrmann, erschienen in Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders 26 (2021): 379‒386 (by Piotr Gotówko) Marcel Knyżewski. Siedziby średnich i niższych rangą urzędników krzyżackich na terenie dzisiejszej Polski. Studium archeologiczne. Monografie Instytutu Archeologii Uniwersytetu Łódzkiego. Vol. 11. Łódź: Wydawnictwo Uniwersytetu Łódzkiego, 2020 (by Marcin Wiewióra) The Templars. The Rise, Fall, and Legacy of a Military Religious Order. Edited by Jochen Burgtorf, Shlomo Lotan, and Enric Mallorquí-Ruscalleda. The Military Religious Orders: History, Sources, and Memory. London–New York: Routledge, 2021 (by Magdalena Satora) Norbert Delestowicz. Bracia zakonu krzyżackiego w Prusach (1310‒1351): studium prozopograficzne. Wydawnictwo Avalon: Kraków, 2021 (by Marcin Sumowski) Akkon – Venedig – Marienburg. Mobilität und Immobilität im Deutschen Orden. Vorträge der Tagung der Internationalen Historischen Kommission zur Erforschung des Deutschen Ordens in Venedig 2018. Herausgegeben von Hubert Houben. Quellen und Studien zur Geschichte des Deutschen Ordens 86 / Veröffentlichungen der Internationalen Historischen Kommission zur Erforschung des Deutschen Ordens 19. Weimar: VDG, 2022 (by Gregory Leighton) László Pósán. Hungary and the Teutonic Order in the Middle Ages. Translated by Andrew Gane. Arpadiana 6. Budapest: Eötvös Loránd Research Network, 2021 (by Gregory Leighton) Dokumenty pokoju brzeskiego między Polską i Litwą a Zakonem Krzyżackim z 31 grudnia 1435. Edited by Adam Szweda, Marcin Hlebionek, Sobiesław Szybkowski, and Janusz Trupinda. Co-editors: Rimvydas Petrauskas and Sergey Polekhov. Toruń: Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2021 (by Janusz Grabowski) Documents concerning Central Europe from the Hospital’s Rhodian Archives, 1314‒1428. Edited by Karl Borchardt. The Military Religious Orders: History, Sources and Memory. London‒New York: Routledge, 2021 (by Jürgen Sarnowsky) Helen J. Nicholson. The Knights Templar. Leeds: Arc Humanities Press, 2021 (by Jürgen Sarnowsky) Deutschordensgeschichte aus internationaler Perspektive. Festschrift für Udo Arnold zum 80. Geburtstag. Herausgegeben von Roman Czaja und Hubert Houben. Quellen und Studien zur Geschichte des Deutschen Ordens 85. Imtal-Weinstraße: VDG, 2020 (by Alexander Baranov) Piotr Szczurowski. Podbój Prus w XIII wieku. Przyczyny „krzyżackiego” sukcesu. Sandomierz: Armoryka, 2019 (by Krzysztof Kwiatkowski) Castra Terrae Culmensis. Na rubieży chrześcijańskiego świata. Vol. 1‒2. Edited by Marcin Wiewióra. Toruń: Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2020 (by Krzysztof Kwiatkowski)